Poly (ADP-ribose) Polymerase Promoter Hypermethylation Predispose Females to Breast Cancer - Sabit, Hussein; Nazir, Shaimaa; Abdel-Ghany, Shimaa; A. Said, Osama; W. Mohammed, Eman; M. Badawy, Omnia; l-zayyat, Ashraf; I. Alqosaibi, Amany; Cevik, Emre; Tombuloglu, Huseyin; Elzawahri, Mokhtar (Asian Pacific Journal of Cancer Biology, 2019)
Being the most common cause of female deaths worldwide, breast cancer (BC) is intensively studied over the last two decades. In the present investigation, we evaluated the promoter methylation of three cancer-related genes; PARP-1, p21, and Rb in 10 bi-matched BC samples (ductal carcinoma and lobular carcinoma) included the core tumor and the adjacent normal tissue. H&E-stained histopathological sectioning revealed grade 2 and grade 3 tumor cells. Methylation-specific PCR (MSP) was performed using methylated (M) and unmethylated (U) primers for the three genes understudy. Histone acetyltransferase was measured in tumor and healthy tissues. A variation in the methylation state of the promoter region of the three genes were observed in core tumor and healthy tissue. PARP and Rb were hypermethylated in tumor tissues while p21 was partially methylated. HAT activities were positively correlated with the methylation pattern observed in healthy tissues, as HAT was highly expressed in healthy vs. tumor tissues. The obtained data might indicate that patients might be at risk of BC recurrence after being subjected to mastectomy. These data could be employed as a core in epigenetic-based data mining to establish a model for predicting the breast cancer-predisposed patients. However, further investigations are needed to fulfill this goal.